The Manila Elementary School Center for the Arts (MESCA) a descriptive analysis - Ong, Telly Palmero
This study examined the implementation from 1982-1987 of the Experimental Program of the Manila Elementary School Center for the Arts. Data were obtained through questionnaires, interviews, observation, and documentary analysis. The MESCA arts teachers use a variety of teaching techniques and instructional materials favoring the creative and interdisciplinary approaches. Students were evaluated through teacher observation, reports, performance data and tests. They were also given opportunities to perform in cultural shows, art competitions, and exhibits. Teachers were trained adequately under the MESCA Executive Committee. However, the implementation was limited to available financial resources. In general, the MESCA Experimental program has been adequately implemented in terms of the salient features embodied in its project proposal.
Thesis (M.Music)--University of the Philippines, Diliman.
Keywords: Gifted children -- Education -- Philippines